A comparative analysis of the diagnostic performances of four clinical probability models for acute pulmonary embolism in a sub-Saharan African population: a cross-sectional study - Esiéné, Agnès (BMC Pulm Med, 2019)
BACKGROUND: The diagnosis of acute pulmonary embolism (PE) is one of the most challenging in emergency settings where prompt and accurate decisions need to be taken for life-saving purposes. Here, the assessment of the clinical probability of PE is a paramount step in its diagnosis. Although clinical probability models (CPM) for PE are routinely used in emergency departments (EDs) of low-resource settings, few studies have cited their diagnostic performances in sub-Saharan Africa (SSA). We aimed to comparatively assess the accuracy of four CPM in the diagnosis of acute PE in sub-Saharan Africans. METHODS: We carried out a cross-sectional study to compare the sensitivity, specificity, positive and negative predictive values and accuracy of four CPM namely; the Wells, simplified Wells, revised Geneva and the simplified revised Geneva (SRG) Scores to computed tomography pulmonary angiography (CTPA) in all adults patients with suspected PE admitted to the EDs of the Gynaeco-obstetric and Paediatric Hospital of Yaoundé and the Yaoundé Central Hospital in Cameroon between January 1, 2017 and April 30, 2018. RESULTS: In total, we enrolled 30 patients with clinical suspicion of acute PE. PE was confirmed on CTPA in 16 (53.3%) cases. Their mean age was 53.7 ± 15.5 years and 36.7% were males. All four scores had a diagnostic performance superior to 50% in all criteria assessed. The simplified Wells score had the highest sensitivity (62.5%) followed by the Wells score (56.3%). The SRG score had the highest specificity (71.4%). The score with highest PPV was the SRG score (66.7%) and that with the highest NPV was the Wells score (56.3%). Overall the models with the highest accuracies were the Wells and SRG scores (60% for each). CONCLUSION: All CPM had a suboptimal diagnostic performance, perhaps highlighting the need of a more optimal CPM for acute PE in SSA. However, the Wells and the SRG scores appeared to be most accurate than the other two scores in the ED. Hence, both or either of them may be used in first intention to predict PE and guide which ED patients should undergo further investigations in an emergency SSA setting.